Analisis Pengaruh Kondisi Internal Dan Eksternal Terhadap Tingkat Pengembalian Saham Pada Perusahaan Perbankan Yang Terdaftar Dalam Bursa Efek Indonesia (BEI) - Fendy Cuandra; Merina Merina (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This study aims to determine whether there is a significant influence of the internal and external conditions of banking companies on stock returns. The internal conditions in this study consist of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Debt to Equity Ratio (DER). Furthermore, the external conditions referred to are inflation and interest (BI Rate). This study used SPSS version 26 program for descriptive statistics analysis, then continued with testing using the E-Views version 10 program to analyze the relationship between variables. Based on the result of hypothesis testing with E-Views, the results show that the CAR and DER variables have a significant positive effect on stock return, while LDR has a significant negative effect. For the NPL and inflation variables on stock returns, the results show that there are not significant effect with negative coefficient. And interest (BI Rate) does not have a significant effect with a positive coefficient